(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The purpose of this paper is to analyze the feminine images and representations outlined in "Mi niñez" (My childhood), an autobiographical work by the Salta artist Carmen Rosa San Miguel de Aranda. In this regard, we are interested in the thematic axes of her narrative, the process of defining a value repertoire and the dialectical construction that unfolds between her life story and her personal identity. This analysis, of the content of her stories and the forms that her narrative acquires, will allow us to approach the subjectivity and the own experience of our autobiographer and to unravel the agreements and tensions between these components and the canonized feminine models constitutive of the Salta culture of the early twentieth century.